2016
DOI: 10.1111/gbb.12264
|View full text |Cite
|
Sign up to set email alerts
|

The D1 family dopamine receptor, DopR, potentiates hind leg grooming behavior in Drosophila

Abstract: Drosophila groom away debris and pathogens from the body using their legs in a stereotyped sequence of innate motor behaviors. Here, we investigated one aspect of the grooming repertoire by characterizing the D1 family dopamine receptor, DopR. Removal of DopR results in decreased hind leg grooming, as substantiated by quantitation of dye remaining on mutant and RNAi animals vs. controls and direct scoring of behavioral events. These data are also supported by pharmacological results that D1 receptor agonists f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…Dopamine receptor activation elicits grooming in flies ( 28 30 ). Grooming is reduced in fumin flies; in addition, when introduced into a novel environment, fumin flies display substantially reduced head grooming in the first 5 min ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Dopamine receptor activation elicits grooming in flies ( 28 30 ). Grooming is reduced in fumin flies; in addition, when introduced into a novel environment, fumin flies display substantially reduced head grooming in the first 5 min ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Future experiments will therefore expand our initial analysis by mapping the DopR requirement in the brain using the DopR f02676 allele, which contains a UAS element for restoration of DopR function when crossed to Gal4 lines (Lebestky et al, 2009; Kong et al, 2010; Pitmon et al, 2016), as well as parallel loss of function experiments utilizing the UAS-DopR-RNAi reagent to isolate the DopR function in discrete circuits of the adult Drosophila brain (Keleman et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The dominant hypomorphic mutant allele DopR f02676 contains a piggy-Bac element insertion with a UAS sequence in the first intron (Exelixis Collection at Harvard medical School). The DopR f02676 allele was backcrossed into the CS wild-type background for six generations (Pitmon et al, 2016). Fly stocks were maintained at 18°C, and crosses were grown at 25°C.…”
Section: Methodsmentioning
confidence: 99%
“…All 4 types of receptors are expressed in the mushroom bodies (Deng et al, 2019). Previous studies showed that Dop1R1 is involved in aversive and appetitive olfactory learning, arousal level regulation, innate and startle-induced motor control, and temperature preference behaviors (Kim et al, 2007;Han et al, 2008;Lebestky et al, 2009;Kong et al, 2010;Bang et al, 2011;Pitmon et al, 2016;Sun et al, 2018). Dop1R2 plays a role in olfactory memory formation and courtship drive (Berry et al, 2012;Zhang et al, 2016).…”
Section: Dop1r1 and Dop2r Are Involved In Flies' Anti-instinctive Leamentioning
confidence: 99%